Confucian Masculinity: State Advocacy of Active Fatherhood in Singapore. (April 2021) - Lim, Adelyn
This article examines representations of fathers and fatherhood in the advertising campaigns of Singaporean government agencies. The introduction of paternity leave and encouragement for fathers to play a bigger role in childcare and child-raising suggest that the government is sympathetic to the pursuit of gender equality, but I argue that state advocacy of active fatherhood serves to reinforce patriarchal tendencies in Singapore. Current scholarship on the problematization of women in state discourses has highlighted the power and privilege of a particular social group in Singapore: heterosexual men. However, there has been a developing body of theoretical and empirical research that looks more critically at the discursive constructions of masculinities, particularly along the dimensions of class, race, and sexuality. This article takes up this issue of different masculinities and the implications this diversity has for understanding patriarchal culture and its intersecting hierarchies. I propose the concept of Confucian masculinity to explain how the depiction of active fatherhood reinforces the ubiquitous "normal family" that upholds patriarchal ideology and perpetuates patriarchal power, thereby obscuring the contradictions of class, race, and sexuality that exist in Singapore.